The hybrid BCI - Pfurtscheller, Gert; Allison, Brendan Z.; Bauernfeind, Günther; Brunner, Clemens; Solis Escalante, Teodoro; Scherer, Reinhold; Zander, Thorsten O.; Mueller-Putz, Gernot; Neuper, Christa; Birbaumer, Niels (Frontiers in Neuroscience, 2010)
Nowadays, everybody knows what a hybrid car is. A hybrid car normally has 2 engines, its main purpose being to enhance energy efficiency and reduce CO2 output. Similarly, a typical hybrid brain-computer interface (BCI) is also composed of 2 BCIs or at least one BCI and another system. Such a hybrid BCI, like any BCI, must fulfil the following four criteria: (i) the device must rely on signals recorded directly from the brain; (ii) there must be at least one recordable brain signal that the user can intentionally modulate to effect goal-directed behaviour; (iii) real time processing; and (iv) the user must obtain feedback. This paper introduces some hybrid BCIs which have already been published or are currently in development or validation, and some concepts for future work. The BCIs described classify 2 EEG patterns: One is the event-related (de)synchronisation (ERD, ERS) of sensorimotor rhythms, and the other is the steady-state visual evoked potential (SSVEP). The hybrid BCI can either have more than one input whereby the inputs are typically processed simultaneously or operate 2 systems sequentially, whereby the first system can act as a “brain switch”. In the case of self-paced operation of a SSVEP-based hand orthosis control with an motor imagery-based switch it was possible to reduce the rate of false positives during resting periods by about 50% compared to the SSVEP BCI alone. It is shown that such a brain switch can also rely on hemodynamic changes measured through near-infrared spectroscopy (NIRS). Another interesting approach is a hybrid BCI with simultaneous operations of ERD- and SSVEP-based BCIs. Here it is important to prove the existing promising offline simulation results with online experiments. Hybrid BCIs can also use one brain signal and another input. Such an additional input can be a physiological signal like the heart rate but also a signal from an external device like, an eye gaze control system.